Labor Jurisdiction - Ferro Delgado, Víctor (1983)
This article analyzes the constitutional controversy in Peru regarding the competence of the administrative labor authorities in resolving labor disputes. Article 232 of the Constitution establishes that the justice administration is the exclusive competence of courts and tribunals, which has led to questioning the legitimacy of the administrative labor authorities to resolve labor disputes. In this context, three positions are developed: the incompetence of the labor authorities, the validity of their resolutions without the guarantee of res judicata, and the arbitral jurisdiction as an alternative. The author also examines Legislative Decree No. 140 and Supreme Decree No. 003-83-TR, which grant quasi-judicial powers to labor inspectors, which could constitute an invasion of jurisdictional matters. In view of this, he suggests that the Labor Court should assume competence in labor disputes, ensuring the impartiality and constitutionality of the processes. Along these lines, the author proposes a restructuring of the justice system to strengthen this jurisdiction and limit the judicial powers of inspectors, so as to preserve the specialty of Labor Procedural Law and overcome the problems of congestion and delays in rulings.